Criteria for topdressing nitrogen application to common bean using chlorophyll meter - Mendonca Maia, Suelen Cristina; Soratto, Rogerio Peres [UNESP]; Liebe, Suzane Maria [UNESP]; Almeida, Adriana Queiroz de (Empresa Brasil Pesq Agropec, 2017)
The objective of this work was to establish the diagnostic leaf and the nitrogen sufficiency index (NSI) values most appropriate to estimate N requirement by the 'Perola' common bean (Phaseolus vulgaris), based on chlorophyll meter monitoring. The diagnostic leaf was defined in an experiment with five N rates, and up to four sampling dates of the diagnostic leaves were evaluated (first, second, and third completely expanded leaves from the apex). The NSI was established in two crop seasons, under six N managements: M1, 40 kg ha(-1) N at sowing + 80 kg ha(-1) 10 days after emergence (DAE) + 80 kg ha(-1) 20 DAE (reference rate); M2, 20 kg ha(-1) at sowing + 40 kg ha(-1) 10 DAE + 40 kg ha(-1) 20 DAE (recommended rate); M3, 20 kg ha(-1) at sowing + 30 kg ha(-1) when NSI<96%; M4, 20 kg ha(-1) at sowing + 30 kg ha(-1) when NSI<93%; M5, 20 kg ha(-1) N at sowing + 30 kg ha(-1) when NSI<90%; and M6, without N application. The relative chlorophyll index readings on the second fully expanded leaf, at 21 DAE, and on the third leaf, at 28 and 35 DAE, are more precise to estimate the requirement of N by common bean. The NSI of 90% is more effective than the NSI of 93 or 96% for defining the moment for N topdressing application.
Keywords: Phaseolus vulgaris; diagnostic leaf; nitrogen fertilization; nitrogen sufficiency index; nitrogen use efficiency; relative chlorophyll index